Three‐year analysis of repeated laboratory tests for the markers total cholesterol, ferritin, vitamin D, vitamin B12, and folate, in a large research and teaching hospital in Italy. Issue 3 (12th January 2017) - Lanzoni, Monica; Fornili, Marco; Felicetta, Irene; Maiavacca, Rita; Biganzoli, Elia; Castaldi, Silvana
Abstract: Rationale, aims and objectives: The increasing number of diagnostic tests requests all over the world is a problem that can partially be explained by inappropriate testing. Impact on the total costs of health systems becomes relevant when tests are performed in a large amount. In this paper, retesting of total cholesterol, ferritin, vitamin B12, vitamin D, and folate is assessed. Methods: The Quality Unit of Fondazione IRCCS Ca' Granda Ospedale Maggiore Policlinico di Milano (Fondazione) decided to perform a first assessment of the appropriate use of the laboratory tests cholesterol, ferritin, vitamin B12, vitamin D, and folate focusing on the retesting interval for the same patient in the time period January 1, 2012, to December 31, 2014, in every care setting. The minimum retesting intervals were chosen following the ACB recommendations. The Fondazione is a research and teaching hospital with 3 emergency units (adult, pediatric, and obstetric), kidney, liver, lung, cornea, and bone marrow transplant centers and a medical school. Record linkage of laboratory records selected for the time interval January 1, 2012, to December 31, 2014, was applied using tax code. For each marker, the distribution of retesting intervals was evaluated for every year and the total period. With the same record linkage variable, requests on inpatients were identified from hospital discharge records. A cost analysis of inappropriate retesting was performed for every test. Results: We examined 466 035 requests for 113 019 patients. Proportions of tests judged potentially inappropriate varied between 8.1% for 1, 25‐dihydroxy vitamin D and 37.1% for total cholesterol. The rates of inappropriate tests from year to year never showed significant decrease, and the maximum increase corresponded to an odds ratio of 1.85 (95% CI, 1.36‐2.51) for 1, 25‐dihydroxy vitamin D from 2012 to 2013. Calculated loss of money was approximately €500 000 in the 3 years. Conclusions: Inappropriate requests represent a waste of time and money resources. Our analysis highlighted economically unacceptable rates of inappropriate retesting, with no evidence of decreasing trend. Actions to raise awareness in clinicians or automated electronic solutions are necessary to limit unnecessary test repetitions.